Daz Studio to VRM pipeline: a discussion on the use of realistic VRM 3D models in upper body motion tracking - Fernandes, Roberta; Silveira, Ismar Frango (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR), 2025)
In recent years, especially after the pandemic, virtual reality avatars and virtual counterparts have experienced a surge in popularity, due to their usefulness in settings where people don’t, or can’t, see each other frequently. However, there are still very few ways to actually create such avatars that offer realism and ways to customize that are low-cost and available to the general public. This paper explores the process of converting photorealistic models created in DAZ Studio to VRM and achieves an end result that can be used in virtual reality, the metaverse, and live motion tracking applications.